ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI KEPERCAYAAN DIRI - Andi Mariani Ramlan; Hermayani Hermayani; Jahring Jahring (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Mathematical problem solving abilities and students' self-efficacy are still not optimal, so they need to be studied. This study aimed to describe the mathematical problem solving ability of class IX students of SMP Negeri 1 Baula in terms of self-efficacy. The type of this research was qualitative. The research subjects were 56 students of class IX SMP Negeri 1 Baula. The instruments were in the form of a self-efficacy questionnaire (18 statement items), 3 test questions of mathematical problem solving abilities, and interview guidelines. Data analysis covered data reduction, data presentation and drawing conclusions. There were three findings in this study as follows. Firstly, students' self-efficacy from 56 students consisted of high self-efficacy (6 students), medium (24 students), and low (26 students). Secondly, the number of students whose problem solving ability were being measured was in high category (5 students), medium category (24 students), and low category (27 students). And lastly, the students with high self-efficacy and high problem solving ability were able to meet the four indicators of problem solving ability. The students with moderate self-efficacy and moderate problem-solving abilities were less able to meet the four indicators of problem-solving abilities. While the students with low self-efficacy and low problem solving ability were not able to meet the four indicators of problem solving ability. So it can be concluded that the higher the students' self-efficacy is, the easier the students solve the problems. On the other hand, the lower the student's self-efficacy is, the more difficult the students solve the problems.